STEPNCMillUoA: A CNC system based on STEP-NC and Function Block architecture - Minhat, Mohamad; Vyatkin, Valeriy; Xu, Xun (Inderscience Enterprise Ltd., 2009)
STEPNCMillUoA is the prototype of a new CNC system that utilises the STEP-NC data model and IEC 61499. STEP-NC provides a high-level data model and enables feature-based machining whereas the enabled layered Function Block architecture simplifies the design of the CNC controller. The architecture layers are responsible for data processing, storage and execution. The object-oriented Model-View-Control design pattern supports the system architecture and the design framework, in which simulation of the machining becomes natural and inherent part of the design process, with seamless transition from simulation to actual machining. This system possesses interoperability, portability, re-configurability and distribution characteristics. The system was tested through simulation and actual machining